2012
DOI: 10.1590/s0100-69162012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Perdas de solo, matéria orgânica e nutrientes por erosão hídrica em uma vertente coberta com diferentes quantidades de palha de cana-de-açúcar em Guariba - SP

Abstract: RESUMO:A erosão em entressulcos resulta da desagregação causada pelo impacto das gotas de chuva na superfície do solo e pelo transporte superficial das partículas do solo desagregadas, onde se encontram a matéria orgânica e os nutrientes fundamentais para a produção agrícola. O presente trabalho teve como objetivo avaliar as perdas de solo, matéria orgânica e nutrientes em uma vertente localizada em uma área de Latossolo Vermelho-Amarelo distrófico, cultivada com cana--de-açúcar, que é colhida mecanicamente. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 10 publications
4
19
0
23
Order By: Relevance
“…These differences are probably due to the erodibility of the soil and straw amount applied per plot. The sediment concentrations decreased with the increase of soil surface coverage with sugarcane, such behavior also corroborates with the results obtained by SOUSA et al (2012).…”
Section: Interrill Erosionsupporting
confidence: 91%
See 1 more Smart Citation
“…These differences are probably due to the erodibility of the soil and straw amount applied per plot. The sediment concentrations decreased with the increase of soil surface coverage with sugarcane, such behavior also corroborates with the results obtained by SOUSA et al (2012).…”
Section: Interrill Erosionsupporting
confidence: 91%
“…The effectiveness of soil coverage to reduce erosion was also observed by SOUSA et al (2012) that when evaluated soil losses of organic matter and nutrients in area with sugarcane cultivation, subjected to mechanical harvesting, using plots with different coverage percentages, concluded that in the plots with 75 % and 100% of coverage, the erosion losses were significantly reduced.…”
Section: Interrill Erosionmentioning
confidence: 98%
“…Quanto à manutenção total da palha (cana-crua), sabe-se que ela é benéfica à proteção do solo, à infiltração e ao armazenamento de água, bem como à ciclagem de nutrientes (Peres et al, 2010;Sousa et al, 2012;Trivelin et al, 2013). A respeito da ciclagem, há variações na liberação de nutrientes pela decomposição, o que, por sua vez, é influenciado pelas condições edafoclimáticas e pela qualidade (nutrientes, celulose, hemicelulose e lignina) do resíduo depositado (Cotrufo et al, 2009).…”
Section: Introductionunclassified
“…Pesquisas recentes sobre o desenvolvimento de indicadores de impactos globais do uso e da ocupação do solo (Santos et al, 2011;Sousa et al, 2012;Matias et al, 2013) evidenciam a necessidade de informações mais detalhadas e menos subjetivas.…”
Section: Introductionunclassified